Penilaian Kapabilitas Manajemen Risiko Teknologi Informasi Menggunakan Kerangka Cobit 5 (Studi Kasus: Daerah Operasional (DAOP) XX) - Nadya Mardiana Rahmania; Suprapto Suprapto; Andi Reza Perdanakusuma (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
Operational Area VIII Surabaya or abbreviated as DAOP XX or DAOP XX is one of the Indonesian railways operating areas, under the environment of PT Kereta Api Indonesia (Persero) under the Board of Directors of PT Kereta Api Indonesia.DAOP XX has a unit engaged in information technology namely the information system unit. The well-developed technology in DAOP XX makes almost all of its business processes computerized and standardized by ISO, but in practice there are still some obstacles in infrastructure management, risk prevention and control. Therefore, It was necessary to a pssess risk management capabilities using the COBIT 5 framework. In the assessment 3 subdomain were selected. These were EDM03 (Ensure Risk Optimisation), APO12 (Manage Risk) and DSS02 (Manage Service Request and Incident). Capability assesment was done through 3 types of data retrieval ie, questionnaires, interviews and observation. From the results of the assessment, it was concluded that the capability value of each subdomain was 2 with the gap value of 1. The recommendation was given to the three subdomains in order to reach the target level. There were 6 recommendations for the EDM03 subdomain.There were further 6 recommendations for the APO12 subdomain and 3 recommendations for the DSS02 subdomain.